The obstacles and problems faced by the coaches of the Premier League in football for the 2009-2010 season according to the coaches’ perspective - Abdul, Kazim (Journal of Physical Education, 2023)
The research aim at identifying the problem that hinder the coaches` work from the coaches `point of view . The study included six fields: coaches, players, club, federation, media, organization and finance of the sport. The researcher used scanning metod on 36 club coaches of 2009-2010 sezonThe researcher came up with many conclusions including the following:-1- Psychological pressure on chaos and interfering in their affairs as wellas firing them in cases of losing . 2- The clubs do not own fields of their own and some of them don’t even have places for practices which affect their artistic level and the coaches’ work . 3- Not activating the coaches’ committee rights in addition to not holding raining courses . 4-There is no league for all age groups . 5- Harsh criticism. Of coaches by the media smatter that places great pressure on the coach which he negatively reflects on his players .6-There is no financial income because of the low level of teams.